ChemInform Abstract: Carbon‐Free Cathodes: A Step Forward in the Development of Stable Lithium—Oxygen Batteries. Issue 7 (January 2016) - Landa‐Medrano, Imanol; Pinedo, Ricardo; Ortiz‐Vitoriano, Nagore; de Larramendi, Idoia Ruiz; Rojo, Teofilo
Abstract: Review: altenatives including metal oxides, noble metals, carbides/nitrides, polymers, and silicenes; 104 refs.